2012
DOI: 10.1371/journal.pone.0036353
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenesis in the Pacific Oyster Crassostrea gigas: A Microarrays-Based Analysis Identifies Sex and Stage Specific Genes

Abstract: BackgroundThe Pacific oyster Crassostrea gigas (Mollusca, Lophotrochozoa) is an alternative and irregular protandrous hermaphrodite: most individuals mature first as males and then change sex several times. Little is known about genetic and phenotypic basis of sex differentiation in oysters, and little more about the molecular pathways regulating reproduction. We have recently developed and validated a microarray containing 31,918 oligomers (Dheilly et al., 2011) representing the oyster transcriptome. The appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 83 publications
(128 reference statements)
3
88
0
Order By: Relevance
“…Despite strong difference in expression levels between sexes, as previously reported [53], we nonetheless detected a clear difference in expression levels between progenies of oysters originated from France and Denmark, and their hybrids. From the RDA approach on microarrays we found that 4.3 % of the explained variance is ascribed by the progeny in a mainly orthogonal way to sex differences, which means that despite the huge transcriptomic differences between sexes, the more modest differences between progenies proved to be mainly independent of the sex.…”
Section: Discussionsupporting
confidence: 66%
“…Despite strong difference in expression levels between sexes, as previously reported [53], we nonetheless detected a clear difference in expression levels between progenies of oysters originated from France and Denmark, and their hybrids. From the RDA approach on microarrays we found that 4.3 % of the explained variance is ascribed by the progeny in a mainly orthogonal way to sex differences, which means that despite the huge transcriptomic differences between sexes, the more modest differences between progenies proved to be mainly independent of the sex.…”
Section: Discussionsupporting
confidence: 66%
“…When these signaling pathways are deregulated, animals are less fertile [28,29]. In the past, gonad differentiation and development in oysters were studied by measuring the expression of genes potentially involved in reproduction (for example, CG-FOXL2 [30,31], CG-DML [32], vasa (termed oyvlg) [5], or OG-TGF beta [33,34]) or elements belonging to the insulin pathway [16][17][18], and recently by a genome-wide expression profiling that identified gonad-and sex-specific genes and potential markers of early sex differentiation in C. gigas [35]. Despite this work, however, our understanding of the mechanisms of the regulation of gonad development versus storage tissue is still limited [36].…”
Section: Introductionmentioning
confidence: 99%
“…Since these first reports, the role of FOXL2 as a master regulator of ovarian differentiation has been abundantly described in various vertebrate species, such as fish [Baron et al, 2004;Nakamoto et al, 2006;Liu et al, 2007;Yamaguchi et al, 2007;Amberg et al, 2010;Hu et al, 2014;Liu H et al, 2015;Wang et al, 2015], amphibians [Oshima et al, 2008;Okada et al, 2009], reptiles [Rhen et al, 2007;Alam et al, 2008;Moore et al, 2010;Shoemaker-Daly et al, 2010], and birds [Govoroun et al, 2004]. More recently, FOXL2 ovarian expression was also reported in invertebrate species, such as crustaceans [Ma et al, 2012;Meng et al, 2015] and molluscs [Dheilly et al, 2012;Liu et al, 2012;Zhang et al, 2014;Shi et al, 2015]. In total, ovary-specific FOXL2 expression has been described in more than 40 species.…”
Section: Identification Of Foxl2 As An Ovarian Factormentioning
confidence: 99%